ANALISIS HUBUNGAN CORPORATE SOCIAL RESPONSIBILITY DAN AGRESIVITAS FINANCIAL REPORTING TERHADAP AGRESIVITAS PAJAK DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - YAHYA .; DARMANSYAH .; M. ARDIANSYAH SYAM (JURNAL ILMIAH KOHESI, 2021)
This study aims to examine empirical evidence related to the analysis of the relationship between corporate socialresponsibility and financial reporting aggressiveness against tax aggressiveness with good corporate governance as amoderating variable during the 2014-2018 period in various industrial sectors and consumer goods industries listed inIndonesia Stock Exchange. The sampling method used in this study was purposive sampling with a sample size of 51companies. The data analyzed in this study consisted of annual reports and financial statements of company. The analysistechnique used is descriptive analysis and statistical analysis with the SPSS program version 24. The result reveal thatcorporate social responsibility is proven to have an influence on tax aggressiveness, financial reporting aggressiveness hasno influence on tax aggressiveness, good corporate governance proxied by independent commissioners and auditcommittees has no negative influence on tax aggressiveness, corporate social responsibility strengthened by independentcommissioners and committees. audit does not have a negative influence on tax aggressiveness, financial reportingaggressiveness which is strengthened by independent commissioners and audit committee does not have a negativeinfluence on tax aggressiveness.